EVALUATION OF INTRAPLACENTAL VILLOUS MICROVASCULAR DENSITY AND VASCULAR SURFACE AREA IN PREGNANCY INDUCED HYPERTENSION AND ITS CORRELATION TO NEWBORN BODY WEIGHT (Iraqi Journal of Medical Sciences, 2016)
Background: Preeclampsia is a major problem in obstetric practice; it is considered one of the largest causes of maternal and perinatal morbidity and mortality, and one of the most important causes of intrauterine growth restriction and low birth weight.Objectives:To evaluate the intraplacental villous microvascular density and vascular surface area in pregnancy induced hypertension in term placentae, and its effect on newborn body weight.Methods:A sample of 50 placentae divided into 25 normal term placentae (Control group) and 25 term placentae of pregnancy induced hypertension (preelampsia) considered as the (Test group). Fresh placental tissues were taken from the peripheral placental area, processed to paraffin blocks, stained with CD-34 (clone QBEnd-10) (DAKOCYTOMATION), assessment of the vascular density, and vascular area with image j software.Results:Significant increase in vascular density, with a significant reduction in vascular area seen in placentae of preeclampsia compared to control group at p ? 0.05, in addition fibrosis with vascular degeneration and stenosis were evident in terminal villi, lead to avascular terminal villi in preeclampsia compared to control group. Significant reduction in newborn body weight in preeclampsia compared to control at p ? 0.05.Conclusions:These results suggested that placenta adapt its structure to maintain its function, this adaptation reflected as an increase in vascular density that consequently occur as uteroplacental perfusion reduces due to maternal vasospasm, and the placenta becomes ischemic as gestation progresses due to hypoxia that affect terminal villi vasculature. Fibrin deposition, vascular degeneration, thickened vessels wall, and stenosis those together reduce the vascular area; these changes accordingly were reflected on newborn body weight in preeclampsia.Key words: Preeclampsia, vascular density, vascular area, placenta.
Keywords: Preeclampsia; vascular density; vascular area; placenta